The lichen family Physciaceae in Thailand—II. Contributions to the genus Heterodermia sensu lato - Mongkolsuk, Pachara; Meesim, Sanya; Poengsungnoen, Vasun; Buaruang, Kawinnat; Schumm, Felix; Kalb, Klaus (Phytotaxa, 2015)
A revision of 245 Heterodermia s.lat. collections from Thailand preserved in RAMK, herb. F. Schumm and herb. K. Kalb is presented. The 39 species found in this material are assigned to the genera Heterodermia Trevis. s.str. with a lower cortex and Pachysporaria-type ascospores (without sporoblastidia), Leucodermia Kalb, gen. nov., with foliose to subfruticose, linear-elongate, ribbon-like, dichotomously branched lobes, loosely attached to the substrate, without a lower cortex, apothecia often with pruinose discs and Polyblastidium-type ascospores (with sporoblastidia) and Polyblastidium Kalb, gen. nov. distinguished by a foliose thallus attached to the substrate, no lower cortex and mostly Polyblastidium-type ascospores. The remaining species are assigned to groups without a formal generic name, awaiting further results from molecular phylogenies. The Heterodermia comosa group contains species which are similar to Leucodermia, but differ in having a subfruticose or rosulate thallus with ascending, spathulate or paddle-shaped lobes and the Heterodermia obscurata group which contains species with a fluffy cottony woolly lower surface which is totally or at least partly impregnated by anthraquinones. Standardized descriptions are provided for all the better known Heterodermia species s.str. worldwide and all other species found in the material studied or reported for Thailand in the literature, as well as species which might be expected to occur in the country. The new species, Leucodermia borphyllidiata Kalb & Meesim, similar to L. boryi, but differing in having a phyllidiate thallus is described, and the new combinations, Leucodermia appalachensis (Kurok.) Kalb, L. arsenii (Kurok.) Kalb, L. boryi (Fée) Kalb, L. ciliatomarginata (Linder) Kalb, L. circinalis (Zahlbr.) Kalb, L. fertilis (Moberg) Kalb, L. leucomelos (L.) Kalb, L. lutescens (Kurok.) Kalb, L. vulgaris (Vain.) Kalb, Polyblastidium appendiculatum (Kurok.) Kalb, P. casarettianum (A. Massal.) Kalb, P. corallophorum (Taylor) Kalb, P. dendriticum (Pers.) Kalb, P. fragilissimum (Kurok.) Kalb, P. hypocaesium (Yasuda) Kalb, P. hypoleucum (Ach.) Kalb, P. japonicum (M. Satô) Kalb, P. magellanicum (Zahlbr.) Kalb, P. microphyllum (Kurok.) Kalb, P. neglectum (Lendemer, R.C. Harris & Tripp) Kalb, comb. nov. [Mycobank MB 813853; Basionym: Heterodermia neglecta Lendemer, R.C. Harris & Tripp, The Bryologist 110(3): 490 (2007)], P. propaguliferum (Vain.) Kalb, P. queenslandicum (Elix) Kalb, P. subneglectum (Elix) Kalb and P. violostriatum (Elix) Kalb, are made. Chaudhuria Zahlbr. is a synonym of Heterodermia s.str. and Chaudhuria indica Zahlbr. is an older synonym for Heterodermia verdonii Elix, but as the name Heterodermia indica (H. Magn.) D.D. Awasthi already exists for another species, the correct name for this taxon reverts to H. verdonii. Chemical analyses revealed that Heterodermia reagens (Kurok.) Elix must be placed into synonymy with Polyblastidium propaguliferum (Vain.) Kalb. Dichotomous keys for the identification of all species are provided. Characteristic TLC profiles for selected species are presented and Rf values for the most important terpenes and pigments are given for the first time in the standard solvents A, B' and C. Photographs showing the species as well as characteristic structures in the genera and groups are also provided. A new epitype for H. comosa from Réunion is designated.